Investigation of metallic adapter sleeves for high throughput dilatometry on spherical micro samples: Untersuchung von metallischen Adapterhülsen für Hochdurchsatz‐Dilatometrie an sphärischen Mikroproben. Issue 1 (30th January 2018) - Cramer, L.; Saddei, P.; Surm, H.; Steinbacher, M.; Zoch, H.W.
Abstract: The rods of an available quenching dilatometer are modified for investigations on spherical micro samples (Ø = 1 mm) via metallic adapter sleeves. The experiments can be seen as preliminary tests for a planned high throughput dilatometer, in which adapters are needed as well. Sleeve geometry and materials are varied in the trials to reproduce the transformation of the micro samples using standardized temperature measuring techniques. Sleeves made out of molybdenum produce the best results because molybdenum has a low and nearly constant thermal expansion up to 700 °C. Sleeves of nickel alloy 36 (Invar) or of an austenitic steel (1.4841) do not produce satisfying results. Thermally induced phase transformations of balls of 100Cr6 and X46Cr13 are successfully measured with the existing dilatometer for common macro samples. First the martensitic transformation is investigated, later the process is verified by the isothermal bainitic transformation of 100Cr6.